Comparison of Gastric Emptying Time after the Ingestion of Whisky with Isocalorically Adjusted Glucose Solution - Tadashi Okabe; Hideo Terashima; Atsuhiro Sakamoto (Journal of Nutrition and Metabolism)
Previous studies have shown that the liquid gastric emptying mainly depended on energy content, regardless of compositional differences. But the gastric emptying of alcoholic beverages remains unclear. Therefore, we performed the present study to compare gastric emptying times between whisky mixed with water and glucose solution with uniform energy contents and volumes. As a crossover study, 10 healthy male volunteers ingested one of 3 test solutions with a uniform volume of 150 ml, i.e., whisky with water-containing whisky 30 ml (67 kcal), sugar water containing glucose 16.8 g (67 kcal), and water (0 kcal), and the gastric emptying time of each beverage was then assessed by ultrasound measurements of the gastric antral cross-sectional area. The gastric emptying pattern of whisky with water was faster than that of isocaloric sugar water, but slower than that of water. Each antral cross-sectional area 20, 30, and 40 min after the ingestion of sugar water was significantly larger than that of whisky with water. Antral cross-sectional areas 10 and 20 min after the ingestion of water were significantly smaller than those of whisky with water. In conclusion, the gastric emptying time of whisky would be faster than that of isocaloric glucose solution and slower than that of water. Unlike the other beverages, the gastric emptying time of alcohol drinks does not purely depend on the energy content because alcohol itself has no calorie before absorption. This study is registered with the University Hospital Medical Information Network (UMIN) Clinical Trials Registry (UMIN000034443).